Tarefas exploratórias-investigativas para a aprendizagem de função afim - Tozo, Fábio Luiz Dias (Universidade Federal de São Carlos, 2016)
The objective of this work was to verify the difficulties of treatments and conversions (natural language, algebraic expressions, tables and graphical form) function of teaching-learning in order to students of the first high school grade of a private school in the city Sorocaba - SP. The study was conducted by means of tasks implemented in three stages; a group of twenty-six students, divided into thirteen doubles. Therefore, we took care to put to task steps, different forms of representation. The theoretical framework was marked in the study of semiotic representation registers, developed by Raymond Duval, and exploratory and investigative tasks, which served also based on the proposal to diversify the methodological procedures used in the teaching function in order. The written production analysis of research subjects sought answer how students of the first high school series have mobilized and coordinated semiotic representation registers in solving exploratory-investigative tasks involving the concept of affine function? The articulation of exploratory-investigative tasks, with the mobilization and coordination of semiotic representation registers, instigated the students to the process of generalization of the concept and characterization of affine function through the use of natural language record in the form of justification. The objective of this work was to verify the difficulties of treatments and conversions (natural language, algebraic expressions, tables and graphical form) function of teaching-learning in order to students of the first high school grade of a private school in the city Sorocaba - SP. The study was conducted by means of tasks implemented in three stages; a group of twenty-six students, divided into thirteen doubles. Therefore, we took care to put to task steps, different forms of representation. The theoretical framework was marked in the study of semiotic representation registers, developed by Raymond Duval, and exploratory and investigative tasks, which served also based on the proposal to diversify the methodological procedures used in the teaching function in order. The written production analysis of research subjects sought answer how students of the first high school series have mobilized and coordinated semiotic representation registers in solving exploratory-investigative tasks involving the concept of affine function? The articulation of exploratory-investigative tasks, with the mobilization and coordination of semiotic representation registers, instigated the students to the process of generalization of the concept and characterization of affine function through the use of natural language record in the form of justification.
Keywords: Ensino médio; Função afim; Registros de representação semiótica; Tarefas exploratórias-investigativas; High school; Affine function; Representation registers semiotics; Exploratory-investigative tasks; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS EXATAS E DA TERRA